2010
DOI: 10.1084/jem.20090348
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus elicits fetal γδ T cell responses in utero

Abstract: The fetus and infant are highly susceptible to viral infections. Several viruses, including human cytomegalovirus (CMV), cause more severe disease in early life compared with later life. It is generally accepted that this is a result of the immaturity of the immune system. γδ T cells are unconventional T cells that can react rapidly upon activation and show major histocompatibility complex–unrestricted activity. We show that upon CMV infection in utero, fetal γδ T cells expand and become differentiated. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(241 citation statements)
references
References 76 publications
12
218
2
1
Order By: Relevance
“…90,91 It is therefore feasible that this change in cd T cell distribution observed in never-infected individuals from this West African population stems from evolutionary selection based on an immune advantage by those having a high proportion of Vd1 T cells-which would again align with the association of there being some adaptive influence of microbial exposure on the make-up of cd T cells in an organism. Other infectious diseases that are associated with the recruitment and expansion of specifically the Vd1 T cell subset in the periphery are cytomegalovirus, 33,92 Epstein-Barr virus 93,94 and HIV. 95,96 In most of these cases, the specific activation and expansion appears to be driven by the presentation of endogenous molecules rather than virally derived antigens-keeping with the notion that these T cells are particularly well adapted to sensing the turmoil within rather than relying exclusively on external validation.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
“…90,91 It is therefore feasible that this change in cd T cell distribution observed in never-infected individuals from this West African population stems from evolutionary selection based on an immune advantage by those having a high proportion of Vd1 T cells-which would again align with the association of there being some adaptive influence of microbial exposure on the make-up of cd T cells in an organism. Other infectious diseases that are associated with the recruitment and expansion of specifically the Vd1 T cell subset in the periphery are cytomegalovirus, 33,92 Epstein-Barr virus 93,94 and HIV. 95,96 In most of these cases, the specific activation and expansion appears to be driven by the presentation of endogenous molecules rather than virally derived antigens-keeping with the notion that these T cells are particularly well adapted to sensing the turmoil within rather than relying exclusively on external validation.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
“…In this context, we and others have shown that Vd2-negative (Vd2 neg ) cd T cells are key effector components in the control of CMV infection (14)(15)(16). This subset, which is typically located within the epithelia, is characterized by the use of Vd1, Vd3 or Vd5 segments (collectively called Vd2 neg cd T cells), whereas the most common subset in the peripheral blood uses the association of Vd2 and Vc9 variable regions (Vc9/Vd2 T cells).…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, in‐utero infection with cytomegalovirus (CMV) has been found to result in in‐utero activation of fetal CMV T cell responses that, compared to adult responses, are ‘functionally exhausted’, with a limited capacity to control CMV replication 50, 51. Although pneumococcal‐specific cord blood cellular cytokine responses were lower overall in infants born to mothers who were pneumococcal carriers at the time of delivery, we were not able to find significant differences compared with responses of infants born to mothers who were non‐carriers: we believe that a more extensive upper respiratory tract pneumococcal carriage study during pregnancy would be needed, including a larger population size to estimate more clearly the effect of maternal carriage on immune priming.…”
Section: Discussionmentioning
confidence: 99%